The Body of the Poem, the Body of the Poet in Urszula Kozioł’s Znikopis - Majca-Lipa, Katarzyna (Representations of Disability in Cultural Spaces, 2026)
This article attempts to analyse Urszula Kozioł’s volume Znikopis, first published as part of the collection Ucieczki (2016) and then as a separate poetry collection (2019). The text of the volume can be read as an elegiac document of gradual departure, an auto-record of the experience of fading away in the physical, emotional and creative dimensions. Aware of the limitations of age, the poet plays with poetic convention: she deconstructs traditional stylistic devices, engages in self-referential reflection on the condition of the poem, and uses irony as a strategy for coming to terms with transience. Kozioł’s works intensify meaning in an economical and subtly nuanced form, revolving around the experience of loss, integration, the physical stitching together of fragments, resistance to passing, departure, the fading of memory, physical and creative abilities. The analysis will conclude that the poet creates an autothematic portrait of the poet’s body and the body of poetry in decay. The works contained in Znikopis are an attempt to organise scattered fragments of language into a coherent whole, and at the same time a gesture of opposition to complete disappearance – of the writing body and the material body.